Audit of adult patients with renal dysfunction presenting to the Charlotte Maxeke Johannesburg Academic Hospital Emergency Department - Masina, John (My University, 2019)
Abnormal renal function is frequently encountered in the emergency department (ED) and may be associated with significant morbidity and mortality (1). Presentation with abnormal renal function may be categorised into i) acute kidney injury (AKI) (2), ii) chronic kidney disease (CKD) (3) and iii) acute on chronic kidney disease (AOCKD) (4). Estimates of the global prevalence ranges from <1% to 66% for AKI (5) and 11% to 13% for CKD (6). Specific data on the epidemiology of renal dysfunction presentation to the ED is scant.
A research report submitted to the Faculty of Health of the University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Emergency Medicine. Johannesburg, 2019
Keywords: Chronic renal failure; Kidney diseases; Kidneys